2003
DOI: 10.2527/2003.81112660x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oscillating dietary crude protein concentration on performance, acid-base balance, and nitrogen excretion of steers1,2,3

Abstract: Decreasing dietary N inputs into beef cattle feeding operations could potentially decrease environmental concerns relating to air and water quality. Previous studies with sheep suggest that oscillating dietary CP concentrations may improve N use efficiency and thereby decrease dietary N requirements. Therefore, two studies were conducted to determine the effects of oscillating dietary CP concentrations on performance, acid-base balance, and manure characteristics of steers fed high-concentrate diets. Steers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 20 publications
8
59
3
Order By: Relevance
“…Previous studies showed that oscillation of the dietary CP improved N retention of ruminants (Collins and Pritchard, 1992;Cole, 1999;Cole et al, 2003). This improvement in the retention of N may provide a viable means to reduce the release of N, especially ammonia, into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that oscillation of the dietary CP improved N retention of ruminants (Collins and Pritchard, 1992;Cole, 1999;Cole et al, 2003). This improvement in the retention of N may provide a viable means to reduce the release of N, especially ammonia, into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Klopfenstein and Erickson 2002). Decreasing dietary protein inputs in feeding could potentially decrease environmental concerns related to air and water quality (Cole et al 2003). Increased P excretion should be avoided by using mineral feeds of low P content together with these by-products.…”
Section: Discussion Feed Intake and Diet Digestibilitymentioning
confidence: 99%
“…Decreasing dietary protein inputs in diet could potentially decrease environmental impacts related to air and water quality (Cole et al, 2003). The P content in some protein supplements, especially in RSM, is high compared with the basal diet based on forages and grains (MTT, 2014).…”
Section: Introductionmentioning
confidence: 99%